2017
DOI: 10.1007/s11239-017-1517-x
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in hospitalization and mortality rates for venous thromboembolism

Abstract: Venous thromboembolism (VTE) is a major health problem for both men and women. Whether sex disparities exist for outcomes after acute VTE is unknown. We sought to measure sex-specific rates of hospitalization for and mortality from acute VTE. We used a population-based administrative dataset from Alberta, Canada, covering the years 2002 to 2012. We used Poisson regression to measure the incidence rate ratio for hospitalization and Cox regression to test for sex disparities in short-term all-cause mortality aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
1
4
0
2
Order By: Relevance
“…Despite sex-specific differences in the prognostic performance of risk stratification markers and models, in the present study, 30-day outcomes did not differ between males and females (Table S1 of the Supplementary material) and were not influenced by the patients' sex. This finding is in accordance with previous cohort studies reporting no differences in shortand long-term mortality in male and female PE patients [13,14,42], while studies using data from nationwide databases observed a higher shortterm mortality rate in female PE patients [11,18].…”
Section: Sex-specific Differences In 30-day Outcomessupporting
confidence: 93%
“…Despite sex-specific differences in the prognostic performance of risk stratification markers and models, in the present study, 30-day outcomes did not differ between males and females (Table S1 of the Supplementary material) and were not influenced by the patients' sex. This finding is in accordance with previous cohort studies reporting no differences in shortand long-term mortality in male and female PE patients [13,14,42], while studies using data from nationwide databases observed a higher shortterm mortality rate in female PE patients [11,18].…”
Section: Sex-specific Differences In 30-day Outcomessupporting
confidence: 93%
“…42,110,111 Other studies have found no significant sex differences in PE-related mortality both short and long term. 46,57,112 Several studies have found that women had higher PE-associated mortality, though in some analyses controlled for severity this difference disappears. Sex-and gender-based differences are recognized in the prevalence, severity, treatment response, and survival of patients with certain types of pulmonary hypertension (PH).…”
Section: Long-term Outcomesmentioning
confidence: 99%
“…Keller et al also found that major bleeding was a significant predictor of all-cause mortality in women [ 22 ]. Despite finding similar results of higher association of female sex with major bleeding and fatal PE, a study based on the RIETE registry demonstrated a loss of these endpoints on multivariate analysis [ 71 ]. Similarly, a separate single-center study showed no sex-based differences in the rate of major bleeding, readmissions, and recurrent PE at 90 days [ 20 ].…”
Section: Resultsmentioning
confidence: 99%